Interfacial Self-Assembly to Spatially Organize Graphene Oxide Into Hierarchical and Bioactive Structures - Majkowska, Anna; Redondo-Gómez, Carlos; Rice, Alistair; Gonzalez, Mariel; Inostroza-Brito, Karla E.; Collin, Estelle C.; Rodriguez-Cabello, Jose Carlos; Del Rio Hernandez, Armando E.; Solito, Egle; Mata, Alvaro (Frontiers in Materials, 2020)
Multicomponent self-assembly holds great promise for the generation of complex and functional biomaterials with hierarchical microstructure. Here, we describe the use of supramolecular co-assembly between an elastin-like recombinamer (ELR5) and a peptide amphiphile (PA) to organise graphene oxide (GO) flakes into bioactive structures across multiple scales. The process takes advantage of a reaction -diffusion mechanism to enable the incorporation and spatial organization of GO within multiple ELR5/PA layers. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and ImageJ software were used to demonstrate the hierarchical organisation of GO flakes within the ELR5/PA layers and the distribution profiles of GO throughout the ELR5/PA membranes. Furthermore, atomic force microscopy (AFM) revealed improved Young's moduli of the ELR5/PA/GO membranes. Lastly, we investigated biocompatibility of the ELR5/PA/GO membrane via various cell culture methods.